The Anticoagulant Effects of the Hookworm, Ancylostoma ceylanicum: Observations on Human and Dog Blood In Vitro and Infected Dogs In Vivo - Carroll, S M; Howse, D J; Grove, D I (Thrombosis and Haemostasis, 1984)
Extracts of adult Ancylostoma ceylanicum prolonged the prothrombin time (PT) and partial thromboplastin time with kaolin (PPTK) of both human and dog plasmas in vitro. Excret-ory/secretory (E/S) products of these worms had similar effects while larval extract prolonged the PTTK only. Thus, the anticoagulant activities of this parasite are dependent upon the stage of the worm’s life cycle. Collagen- and ADP-induced platelet aggregation were inhibited by adult and larval extracts. When the peripheral blood and bleeding times of dogs with varying worm burdens were examined, the only abnormality was shortening of the PTTK in the most heavily infected animals. Homogenates of dog small bowel subjacent to adult hookworms prolonged the PT of dog plasma and electron microscopical examination of this tissue revealed aggregation of platelets in blood venules without fibrin deposition. Thus, this study provides evidence that the anticoagulant properties of hookworms may have biological significance in infected animals.
Keywords: Ancylostoma ceylanicum; Hookworm; Anticoagulant effects